Optimalisasi Peran Pemerintah dalam Pengelolaan Objek Wisata Sungai Sembra di Sorong Selatan - Saflesa, Albert Feneza; Ali, Muhammad; Halik, Wahyudin (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2024)
The aim of this research is to obtain an overview of the role of local government in managing tourist attractions and the factors that influence the management of the Sembra River tourist attraction in South Sorong Regency. This research uses a qualitative approach with a descriptive type of analysis through primary data collected using interviews, observation and literature review methods in accordance with the theme of this research. The research results show that the optimization role of local government is not yet Optimize as a facilitator, regulator, dynamist and catalyst. For further the factors that influence the management of tourist attractions include supporting factors (budget, panorama of tourist attractions and strategic locations) and inhibiting factors (budget limitations, lack of human resources and customary rights).